Generic and scalable method for the preparation of monodispersed metal sulfide nanocrystals with tunable optical properties - Bera, Abhijit; Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K.; Bhagavatula L. V. Prasad (Langmuir, 2018)
A rational synthetic method that produces monodisperse and air-stable metal sulfide colloidal quantum dots (CQDs) in organic nonpolar solvents using octyl dithiocarbamic acid (C(8)DTCA) as a sulfur source, is reported. The fast decomposition of metal-C(8)DTCA complexes in presence of primary amines is exploited to achieve this purpose. This novel technique is generic and can be applied to prepare diverse CQDs, like CdS, MnS, ZnS, SnS, and In2S3, including more useful and in-demand PbS CQDs and plasmonic nanocrystals of Cu2S. Based on several control reactions, it is postulated that the reaction involves the in situ formation of a metal-C(8)DTCA complex, which then reacts in situ with oleylamine at slightly elevated temperature to decompose into metal sulfide CQDs at a controlled rate, leading to the formation of the materials with good optical characteristics. Controlled sulfur precursor's reactivity and stoichiometric reaction between C(8)DTCA and metal salts affords high conversion yield and large-scale production of monodisperse CQDs. Tunable and desired crystal size could be achieved by controlling the precursor reactivity by changing the reaction temperature and reagent ratios. Finally, the photovoltaic devices fabricated from PbS CQDs displayed a power conversion efficiency of 4.64% that is comparable with the reported values of devices prepared with PbS CQDs synthesized by the standard methods.